Envenomation by the Green Bush Viper Atheris squamigera. (2022) - Ontiveros, Sam T.; Srihari, Priya; Winkler, Garret A.; Del Rosso, Jake; Sobel, Julia; Clark, Richard F.; Minns, Alicia B.
Abstract: The Green Bush Viper, Atheris squamigera, is native to West and Central Africa and has few well reported envenomations. Bite victims experience dizziness, nausea, headache, regional lymphadenopathy, and localized edema. Most reports also detail severe effects including thrombocytopenia, coagulopathy, hemolysis, hemorrhage, or renal failure. Fatalities are reported, but poorly described. There is no specific antivenom for A. squamigera, but non-species specific antivenom has been reported helpful in several cases. We report the case of a 36-year-old woman who was bitten by a green bush viper and was treated with several non-species specific antivenoms. There were no complications to antivenom administration and the patient experienced a milder envenomation than detailed in previous reports. Graphical Abstract: ga1 Highlights: The Green Bush Viper has no specific antivenom and envenomation is poorly reported. Local and systemic effects can be seen. Multi-organ failure and severe bleeding reported. Echis antivenoms are reported helpful, but early administration has not previously been reported.